STS Program Planning Committee: Pre-conference Tour of the California Marine Mammal Center and the San Francisco Bay Model - STS Program Planning Committee (Issues in Science and Technology Librarianship)
Announcement of a pre-conference tour of the California Marine Mammal Center and the San Francisco Bay Model on Friday June 26.